Internship program and Students’ skills: A Case of Business Students from the Faculty of Business and development studies, Bishop Stuart University. - Betrum, Namanya; Tamson Nuwagaba; Milton Nuwabimpa (IJRDO - Journal of Business Management, 2019)
Since 1990’s, internship program has gained popularity as an effective approach to enhance student’s employability and career development. In the world of academia, internship is seen as a period in which the students get the hands-on experience, and skills as well as providing a room for students to get what to do after their courses. As a result, internship has become a culture in most of the post- secondary institutions. The study therefore intended to establish the effectiveness of internship program in improving students’ skills using a case of business students in the faculty of business and development studies, Bishop Stuart University-Mbarara. The study was limited to establishing the contribution of internship program in improving hands-on experience and skills development among students, the main challenges hindering the effectiveness of the internship Program in achieving its objectives as well as the main areas of improvement towards effective internship exercise. The study used a sample size of 136 respondents. Data was analyzed both quantitatively and qualitatively. The study findings revealed that internship exercise has played a significant role in enhancing students’ social skills than student’s hands on experience. These social skills include; Interpersonal skills, problem-solving skills, networking skills, identifying potential employers, public communication skills. Students’ hands on experience/skills especially accounting and computer skills were not improved due to inadequate computers against many interns and limited attention given to the interns. The study further found out that there are mediating factors that hinders internship program to achieve its objectives; these included Work environment, organizational culture, students’ attitude and the expertise of the supervisor. The study revealed a number of challenges hindering the effectiveness of the internship exercise. The study recommends that there a need to make a memorandum of understanding between academic institutions and the training agencies so that students can be able to train from relevant departments. The study recognized a need for the government support towards internship programs especially through providing adequate computers to the training agencies.